3D lanthanide-coordination frameworks constructed by a ternary mixed-ligand: crystal structure, luminescence and luminescence sensing. Issue 4 (23rd December 2019) - Xu, Qi-Wei; Dong, Gaoyun; Cui, Ruifang; Li, Xia
Abstract : Highly stable 3D Ln-MOFs were constructed by a ternary mixed-ligand. The Sm/Dy-MOFs present dual-emission while the Tb/Eu-MOFs exhibit red/green MC emission. The detection of quercetin and Fe 3+ ion was realized based on the luminescence Eu-MOF under the excitation of 358 nm. Abstract : Using a mixed ligand synthesis strategy involving semi-rigid 4-(4-carboxyphenoxy)-isophthalic acid (cphtH3 ), oxalate (ox) as a mixed linker and 1, 10-phenanthroline (phen) as an ancillary terminal ligand, a series of highly stable metal coordination frameworks, Ln-MOFs, [Ln(cphtH)phen(ox)0.5 ] n · m H2 O (Ln = Sm 1, Eu 2, Gd 3, Tb 4 and Dy 5 ), were synthesized. They are isostructural 3D coordination networks of interlinked left- and right-handed helices based on [LnO7 N2 ] connections. The Brunauer–Emmett–Teller (BET) surface area was 3.3020 m 2 g −1 (Langmuir surface area: 3.6940 m 2 g −1 ). They are chemically stable in common solvents and are stable in aqueous solutions from pH = 4 to 9. Complexes 1 and 5 are dual-emissive materials exhibiting a broad emission band from the π*–π transition of the organic linker and narrow emission peaks, the 4 G5/2 → 6 H J ( J = 5/2, 7/2, and 9/2) transitions of the Sm 3+ ion for 1 and 4 F9/2 → 6 H J ( J = 15/2 and 13/2) transitions of the Dy 3+ ion for 5 . Complexes 2 and 4 exhibit red and green emission, assigned to the 5 D0 → 7 F J ( J = 1–2) transitions of the Eu 3+ ion and 5 D4 → 7 F J ( J = 6–3) transitions of the Tb 3+ ion, respectively. The maximum excitation wavelengths are 356, 358, 360 and 350 nm for 1, 2, 3 and 4, respectively, which are in the near-visible radiation region (350 nm < λ ex < 420 nm). The Sm-MOF (1 ) displays a single component white light based on its dual-emission. The primary focus of this study is to examine the fluorescence properties of Eu-MOF (2 ) as it showed excellent luminescence in solvent as well as aqueous solutions over a wide pH range (pH = 4–9). Based on the luminescence quenching of the Eu-MOF, the detection of quercetin in water and Fe 3+ ions in several solvent systems was realized at a long maximum excitation wavelength of 358 nm.